UKRAINIAN FOLK DANCE AS A PART OF THE NATIONAL WORLD PERCEPTION - Гапєєв, В. К.; Гапєєва, І. М. (SWorldJournal, 2022)
The materials of theses consider the issues of research and classification of Ukrainian folk dance, its role in the formation of original culture and in particular the worldview of Ukrainians through their attitude to various life situations. The authors